Knjigovodska vrednost kot ocenjena vrednost poslovnega deleža pri izključitvi družbenika iz družbe z omejeno odgovornostjo - Prelič, Saša (Pravnik, 2024)
The partnership agreement, which allows for the contractual exclusion of partners, must specify the conditions, procedure, and consequences of such exclusion. It should also outline the for determining the suitability of the monetary equivalent (severance pay) entitled to the excluded partner, whose business share will be terminated as a result of the exclusion. The social contract may establish the severance pay based on various criteria and standards, which can include measurable data, such as the book value of the business share at a specific point in time. The provision of Article 502 (6) of the Slovenian Companies Act (Zakon o gospodarskih družbah – ZGD-1), which refers to “estimated value”, does not mandate the compulsory execution of an external valuation by independent external appraisers. This is because the concept of “estimated value” may also align with the value of a business share, as determined within the scope of permissible autonomy by the partnership agreement, as deemed appropriate by the partners themselves. Thus, the concept of “assessed value” can also reflect a value based on bookkeeping data on the ratio between the share capital and the share capital(s) of the excluded partner.
Keywords: book value; business share; družba z omejeno odgovornostjo; družbena pogodba; družbenik; knjigovodska vrednost; limited liability company; partner; partnership agreement; poslovni delež; valuation; vrednotenje